Adolescent-Parents Communication on Sexuality in the Context Of HIV/AIDS - Essah, Naa Korkoi (UniMAC-GIJ, 2015)
The dissertation examined adolescent - parents' communication in the context of HIV/AIDS. It sought to bring to light whether the upsurge of HIV I AIDS and other sexually transmitted diseases has made parents responsible for educating their adolescent children on sexuality. The study was occasioned by the epidemiological data which indicated that about half of all global HIV infections occur in young people. This has awakened the fight against HIV/AIDS infections and sexually transmitted diseases in general. Recent studies have indicated that adolescent share information about sexuality more within peers than with parents. However little is known about whether parents are making the efforts of communicating with their adolescent children on sexuality. This study examined this issue. The study adopted a qualitative method with participants being selected thought the purposive criterion sampling. Data were obtained through in-depth interviews with two (2) adolescents children aged 16-19; a boy and a girl respectively with two parents but were not the biological parents of the adolescents interviewed. The results indicated that parents are making the effort of introducing sexuality communication in the home although the adolescent feel they should be taught more or given more detailed information on sexuality. The main issues discussed were pubertal changes, HIV/AIDS and teenage pregnancy. The fact on HIV transmission was discussed in elaborate detail in most families. In sexuality discussion however, parents referred to sexual activities by using vague words and impressions. Discussions were mostly initiated by parents rather the adolescent. This study is different from previous Ghanaian studies on the subject because it has brought to light that Ghanaian parents in Odumase -Krobo are making efforts or attempts in communicating on sexuality issues with their adolescent children. It also brought to light that parent have favourable attitudes towards talking about sexuality and all of them communicated to some extent with their children. It is suggested that parents should start sexuality discussions early to avoid embarrassment in the introduction of the topic when the children reach puberty or adolescents.
MA Media Studies